2016
DOI: 10.1177/1474474016680106
|View full text |Cite
|
Sign up to set email alerts
|

Machine-made lace, the spaces of skilled practices and the paradoxes of contemporary craft production

Abstract: This article inspects a set of paradoxes that appeared in an investigation of contemporary industrial craft in the last remaining factory making machine lace in the United Kingdom. Its focus on a single site, set against a now global industry, means it can build on work in cultural and economic geography to understand this setting as a heterogeneous space, with links to a range of material and immaterial lineages, practices and networks. Ethnographic fieldwork on the factory floor at Cluny Lace threw up three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The other is a developing relationship with a working museum of framework knitting at Ruddington, near Nottingham. The former work used ethnography (Fisher and Botticello 2016) and 3D modelling to uncover some aspects of the human/machine interactions that are necessary to producing lace with a 150-year old technology [Figures 3&4]. It resulted in a short film, 'Twisthands at the Deadstop', which explains the Leavers technology using animation 8.…”
Section: Case-study: Lace Making In the East Midlandsmentioning
confidence: 99%
“…The other is a developing relationship with a working museum of framework knitting at Ruddington, near Nottingham. The former work used ethnography (Fisher and Botticello 2016) and 3D modelling to uncover some aspects of the human/machine interactions that are necessary to producing lace with a 150-year old technology [Figures 3&4]. It resulted in a short film, 'Twisthands at the Deadstop', which explains the Leavers technology using animation 8.…”
Section: Case-study: Lace Making In the East Midlandsmentioning
confidence: 99%
“…The logic underpinning this binary has been challenged by scholars of organisational and management studies (Brown and Duguid 1991;Riege and Zulpo 2007) and human geographers (Carr and Gibson 2016;Fisher and Botticello 2018). Focusing on factory floor workers, service technicians and maintenance and repair staff, they have shown that 'manual' labour is neither unskilled nor bereft of knowledge.…”
Section: Insights From the Factory Floor And Artisan's Workhopmentioning
confidence: 99%
“…They exercise insight and judgement based on "accumulated wisdom", moving beyond instruction manuals or plans (Brown and Duguid 1991, p.45). Their knowing deepens with repetition, trial and error, thinking and doing (Riege and Zulpo 2007;Fisher and Botticello 2018). This body of work unsettles the mind/body binary, asserting that knowledge and skill overlap.…”
Section: Insights From the Factory Floor And Artisan's Workhopmentioning
confidence: 99%
“…The renewed interest in embodiment and the affective and emotional aspects of everyday life within cultural geography has created an opportunity to shift to a finer grain of analysis. Labour geographers attentive to the cultural and ethnographic have thus called for closer analysis of the mundane acts, bodily tasks, emotional terrain, and instances of negotiation and resistance present in concrete workspaces, in the moments of labouring (Fisher & Botticello, ; Herod, Rainnie, & McGrath‐Champ, ; Warren, ). What exactly do bodies do at work?…”
Section: Geographies Of Making As Embodied Labour Processmentioning
confidence: 99%